FAKTOR YANG BERHUBUNGAN DENGAN PENGGUNAAN PARTOGRAF DI KABUPATEN NIAS BARAT - DARNIATI MENDROFA; MINDO TUA SIAGIAN; TONI WANDRA; EVAWANI MARTALENA SILITONGA; DONAL NABABAN (LP2MTBM MAKARIOZ, 2021)
The infant mortality rate in West Nias Regency adi in 2018 there were 8 people, an increase from 6 people in 2017.To find out the relationship between knowledge and attitudes of midwives and the use of partographs in West Nias Regency,a quantitative research was carried out on all midwives working in 13 inpatient health centers in the district. West Nias in2019. Based on human resource data, the number of midwives was 65 people. This study used a cross sectional design.The sample size in this study was the total population of 65 people. This is to determine the relationship between theindependent variables (knowledge and attitudes) and the dependent variable (use of a partograph). The test used is the chisqare test. The results showed that there was a relationship between the knowledge of midwives and the use of partographsin West Nias district. There was a relationship between the attitudes of midwives and the use of partographs in West Niasdistrict. There is a need for more proactive socialization to do socialization or to refresh the education transfer of knowledgeand attitudes of midwives in using partographs to all midwives to avoid bad outcomes in the labor process. Further researchis needed to identify other factors in the use of parographs in West Nias District.